2015
DOI: 10.1089/jcr.2014.0020
|View full text |Cite
|
Sign up to set email alerts
|

Mood and Psychomotor Tremor Changes following Acute Caffeine Consumption in Moderate and Minimal Caffeine Consumers

Abstract: Background: The mood and psychomotor effects of caffeine are well documented; however, many previous studies assessing these factors have been carried out on habitual consumers of caffeine. Thus, it is difficult to discern whether beneficial findings are due to the positive effects of caffeine or the reversal of negative withdrawal symptoms. Aims: The current placebo-controlled balanced-crossover study aimed to investigate the acute effects of caffeine on mood and psychomotor performance in both moderate consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Combined with the location context from GPS logging, the body acceleration can provide unprecedented details about the physiological and health state of an individual. Wilson et al ( 2014 ) showed that even the past medical history of people can be detected via the fine-scale reporting of 3D-acceleration vibrations (Wilson et al 2014 ; Sands et al 2015 ). Similarly, the sickness behaviour of animals—perhaps one of the best remote measurements of health in wildlife—can be inferred from 3D-acceleration loggers (Wilson et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the location context from GPS logging, the body acceleration can provide unprecedented details about the physiological and health state of an individual. Wilson et al ( 2014 ) showed that even the past medical history of people can be detected via the fine-scale reporting of 3D-acceleration vibrations (Wilson et al 2014 ; Sands et al 2015 ). Similarly, the sickness behaviour of animals—perhaps one of the best remote measurements of health in wildlife—can be inferred from 3D-acceleration loggers (Wilson et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used accelerometry to identify micromovements related to caffeine withdrawal and caffeine consumption. 21 Further, we have presented evidence of marked differences in psychomotor control-specifically "tremor" values (vectorial dynamic acceleration 19 )-in MDMA users when they hold their arms horizontally. 18 Flavel et al 20 measured the degree of finger tremor for abstinent amphetamine, MDMA, and cannabis users compared with non-drug users and observed significant impairment in MDMA users.…”
mentioning
confidence: 80%
“…Empirical research investigating the effect of stimulants on motor function using accelerometry is limited. We have previously used accelerometry to identify micromovements related to caffeine withdrawal and caffeine consumption . Further, we have presented evidence of marked differences in psychomotor control—specifically “tremor” values (vectorial dynamic acceleration)—in MDMA users when they hold their arms horizontally …”
mentioning
confidence: 99%
“…Caffeine elicits improvements to multiple cognitive domains including information processing, attention, and specific types of memory 812 . Although caffeine elicits benefits to cognitive domains, concerns associated with increased anxiety/anxiety-like symptoms 13,14 , muscle tremors 15,16 , and withdrawal symptoms 17,18 are present.…”
Section: Introductionmentioning
confidence: 99%